1997
DOI: 10.1002/(sici)1096-9101(1997)20:2<164::aid-lsm7>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nonablative laser energy on the joint capsule: An in vivo rabbit study using a holmium: YAG laser

Abstract: Background and Objective The nonablative application of holmium:yttrium‐aluminum‐garnet (Ho:YAG) laser energy to the joint capsule of patients with glenohumeral instability has been found to shrink capsular tissue and to help stabilize the joint. The purpose of this study was to evaluate the effect of nonablative laser energy on the short‐term histological properties of joint capsular tissue in an in vivo rabbit model. Study Design/Materials and Methods Eighteen mature New Zealand white rabbits were used in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
0
1

Year Published

2001
2001
2004
2004

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(29 citation statements)
references
References 26 publications
1
27
0
1
Order By: Relevance
“…Recently the application of thermal energy as a means to selectively shrink the glenohumeral capsule using an arthroscopic procedure has been advocated. 4,[7][8][9]18 In our current study, we examined the functional outcomes of 130 overhead athletes undergoing TACS at a mean follow-up of 29 months (range, 15-47 months). The results of our study indicate superior outcomes to those which reported using open and arthroscopic stabilization procedures without TACS, 3,12,15,17,20,[22][23][24]29 and similar to those of Savoie and Field, 25 Lyons et al, 16 and Levitz et al, 14 which used TACS.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Recently the application of thermal energy as a means to selectively shrink the glenohumeral capsule using an arthroscopic procedure has been advocated. 4,[7][8][9]18 In our current study, we examined the functional outcomes of 130 overhead athletes undergoing TACS at a mean follow-up of 29 months (range, 15-47 months). The results of our study indicate superior outcomes to those which reported using open and arthroscopic stabilization procedures without TACS, 3,12,15,17,20,[22][23][24]29 and similar to those of Savoie and Field, 25 Lyons et al, 16 and Levitz et al, 14 which used TACS.…”
Section: Discussionmentioning
confidence: 99%
“…The rehabilitation program utilized in this study is based on the authors' clinical experience of over 700 patients treated with TACS between 1997 and 2003, the effects of mobilization on collagen tissue healing, 1,6,34,36 and the basic science of collagen tissue healing following thermal modification. [7][8][9]18,19,[27][28]34 The rehabilitation program follows a gradual progression of applied loads on the collagen tissue to restore range of motion as the strength and tensile properties of the collagen tissue gradually returns to the preoperative state. The use of immediate motion is based on the theory that gentle passive motion is beneficial to the restoration of the organization, alignment, and strength of collagen tissue.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations